2016
DOI: 10.1002/2015jb012456
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of surface mass loading displacement response to perturbations in the elastic structure of the crust and mantle

Abstract: Surface mass loads generate a rich spectrum of deformation responses in the solid Earth that might be exploited to probe the material properties of the crust and mantle. Here we present a detailed examination of load‐induced surface displacements and their sensitivities to systematic perturbations in elastic Earth structure. We compute Love numbers and displacement load Green's functions (LGFs) by integrating the equations of motion for spheroidal deformation of a radially heterogeneous and self‐gravitating Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 51 publications
(158 reference statements)
1
43
0
Order By: Relevance
“…Insights can be gained from modeling results of the elastic response to surface loading. For the case of surface loads on a spherical Earth model, Martens et al [] show that Greens functions for vertical and horizontal surface displacements depend in a different manner on the Earth model and variations in its parameters. If a similar situation arises for the viscoelastic case, then a simplified Earth model fitting horizontal displacements may not necessarily fit equally well the vertical.…”
Section: Discussionmentioning
confidence: 99%
“…Insights can be gained from modeling results of the elastic response to surface loading. For the case of surface loads on a spherical Earth model, Martens et al [] show that Greens functions for vertical and horizontal surface displacements depend in a different manner on the Earth model and variations in its parameters. If a similar situation arises for the viscoelastic case, then a simplified Earth model fitting horizontal displacements may not necessarily fit equally well the vertical.…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest is using geodetic observations of OTL response to constrain allowable models for Earth structure (Ito & Simons 2011;Bos et al 2015;Martens et al 2016aMartens et al , 2019. The theory behind load-induced Earth deformation long predates the ability to measure deformation with sufficient accuracy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Martens et al (2016b) found similarities between predictions and observations even for the small-amplitude principal lunar fortnightly tide (M f ), although measurement uncertainties were larger in this frequency band than for the semidiurnal and diurnal tides. Sensitivity analyses of Earth's response to surface loading indicate peak sensitivities to structure within the crust and upper mantle (Ito & Simons 2011;Martens et al 2016a). As such, OTL-induced deformation provides a valuable opportunity to perform inversions for structure using geodetic data sets that are complementary to traditional seismic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we forward‐model load‐induced surface displacements using the LoadDef software (Martens, Simons, et al, ; Martens, Rivera, et al, ). The predicted displacements are generated by convolving a mass‐load model with load Green's functions that specify the response of a spherically symmetric, nonrotating, elastic, and isotropic Earth to a point‐load of unit mass (Farrell, ).…”
Section: Data Reduction and Methodsmentioning
confidence: 99%